(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
Youth-methods of upbringing in the spirit of military-patriotic education are aimed at the formation in young people of the necessary vital knowledge, skills, skills and strong will, high spiritual and moral qualities, the expression of factors affecting their consciousness, psyche and activity